2020
DOI: 10.1177/0020720920940586
|View full text |Cite
|
Sign up to set email alerts
|

Study on the influence of effective width of roads in the central business district on the evacuation time in case of emergency

Abstract: The central business district is a densely populated area, compared with other evacuation modes, pedestrian evacuation is the most effective evacuation mode in case of emergency. During emergency evacuation, the pace of the crowd and the effective width of the roads are closely relevant. At present, there are differences in the setting of effective width of road in the central business district at home and abroad, and they pay more attention to the general traffic value of road, without too much research and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Leon et al ( 2021) [20] analyzed the effect of network structure on pedestrian evacuation, but ignored the influence of road grade indices. Wang et al (2020) [62] emphasized the influence of road width and type and thought that pedestrian roads were the best for pedestrian evacuation but did not consider the synergy of network structure indices. This study innovatively found the synergy of road network planning indices.…”
Section: Parametric and Synergistic Effect Analysismentioning
confidence: 99%
“…Leon et al ( 2021) [20] analyzed the effect of network structure on pedestrian evacuation, but ignored the influence of road grade indices. Wang et al (2020) [62] emphasized the influence of road width and type and thought that pedestrian roads were the best for pedestrian evacuation but did not consider the synergy of network structure indices. This study innovatively found the synergy of road network planning indices.…”
Section: Parametric and Synergistic Effect Analysismentioning
confidence: 99%